PENGARUH INTEGRITAS, TEKANAN FINANSIAL DAN PERSONAL CULTURE TERHADAP KECURANGAN AKUNTANSI PADA ORGANISASI PERANGKAT DAERAH (OPD) KABUPATEN JEMBRANA - Ni Putu Chika Candra Pramesti; Cokorda Gde Bayu Putra (Hita Akuntansi dan Keuangan, 2020)
Accountingt can help various parties to control company conditions more easily. Accountingt fraud ist thet most important problem thatt happens in Accountingt field. Accountingt fraud ist an act of cheatingt or deviation thatt ist intentionally done by cheating, manipulating, or causingt harm to a company, group, or individutal. This research aims to obtain empirical evidence about thet effect of integrity, financial pressure, andt personalt culturet on accountingt fraud in Jembranat district OPD usingt purposive samplingt method. Thet sample in this research was 28 OPD Jembranat regency with 112 respondentts, thet datat collection method thatt used in this research was a questionnaire method. Thet results showed thatt integrity had no significant effect on accountingt fraud, financial pressure had a positive andt significant effect on accountingt fraud andt personalt culturet had a negative andt significant effect on accountingt fraud.